STUDY PENGOLAHAN SAMPAH ORGANIK DAN ANORGANIK PADA UNIT BANK SAMPAH BADAN USAHA MILIK GAMPONG (BUMG) BLANG KRUENG - Teuku Badlisyah; Siti Agustinur; Maya Rosa (Lantanida Journal, 2022)
This research is entitled "Study of Organic and Anorganic Waste Processing at the Unit Bank Sampah of Badan Usaha Milik Gampong (BUMG) Blang Krueng". One of the environmental problems that still need to be resolved is the waste problem. In general, people immediately throw away or burn garbage without considering the causes and effects that will arise after that. So, one of the waste management methods is organic and inorganic based waste management as practiced by the Waste Bank unit at BUMG Blang Krueng. The formulation of the problem in this study is how to manage organic and inorganic waste in the BUMG Blang Krueng Unit Bank Sampah. This research is a field study research. This is a type of qualitative research using the method of observation, interview and documentation in data collection. Data analysis was carried out descriptively from the results of observational data and documentation obtained. Based on the results of the study, it was found that the BUMG Blang Krueng Unit Bank Sampah had processed organic waste with a composting system so that compost and liquid fertilizers were obtained, as well as inorganic fertilizer processing and recycled materials such as plastic ore and other selling value materials were obtained. Keywords: 1. Processing 2, Organic Waste 3. Inorganic Waste